2016
DOI: 10.1902/jop.2016.160033
|View full text |Cite
|
Sign up to set email alerts
|

Elevated MicroRNA‐128 in Periodontitis Mitigates Tumor Necrosis Factor‐α Response via p38 Signaling Pathway in Macrophages

Abstract: miRNA-128 may be involved in mitigating the inflammatory response induced by P. gingivalis in periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…In the present study, miRNA microarrays were performed to compare the expression of 754 inflammatory‐related miRNAs and no statistical difference was found when CP and AP groups were compared. Current knowledge shows that some studies had examined the expression of miRNAs in inflamed gingival tissues in comparison with healthy gingival tissues (Kalea et al, ; Lee et al, ; Na et al, ; Ogata et al, ; Perri, Nares, Zhang, Barros, & Offenbacher, ; Stoecklin‐Wasmer et al, ; Xie et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, miRNA microarrays were performed to compare the expression of 754 inflammatory‐related miRNAs and no statistical difference was found when CP and AP groups were compared. Current knowledge shows that some studies had examined the expression of miRNAs in inflamed gingival tissues in comparison with healthy gingival tissues (Kalea et al, ; Lee et al, ; Na et al, ; Ogata et al, ; Perri, Nares, Zhang, Barros, & Offenbacher, ; Stoecklin‐Wasmer et al, ; Xie et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This miRNA is involved in many types of cancer, inflammatory and autoimmune diseases, as well as other pathological processes such as leukaemia, rheumatoid arthritis and cardiovascular disease (Eyholzer et al, ; Sugatani & Hruska, ). Gingival tissues from individuals with periodontitis were also recently investigated, and an increased expression of miR‐128, miR‐34a and miR‐381, and a decreased expression of miR‐15b, miR‐211, miR‐372 and miR‐656 were observed (Na et al, ). Although these previous studies showed many differences between miRNAs expression profiles in healthy and diseased individuals, our investigation observed no difference between AP and CP groups, possibly because groups of diseased subjects were compared.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that miR-146a regulated the cytokine secretion in human gingival fibroblasts and periodontal ligament cells [10, 11]. Recent studies from others delineated that miR-128 controlled the inflammatory response in macrophages after stimulated with porphyromonas gingivalis ( P. gingivalis) [12], and miR-24 acted as a negative regulator in the polarization and plasticity of macrophages activated by P. gingivalis LPS or A. actinomycetemcomitans LPS [13]. …”
Section: Introductionmentioning
confidence: 99%
“…To this end, they conducted experiments in which they exposed THP-1 and the oral squamous carcinoma CA9-22 cell lines to P. gingivalis [13]. They subsequently reported increased levels of miR-128 in the THP-1 and the CA9-22 cells [13].…”
Section: Effects Of Mirna-128 On Inflammatory Response In Periodontitismentioning
confidence: 99%